Adenosquamous Carcinoma of Gallbladder with Unusual Prognosis: A Case Report - Siddinath Gyawali; Biraj Pokhrel; Deepak Sharma; Naveen Chandra Bhatta; Bishnu Prasad Kandel; Paleswan Joshi Lakhey (Journal of Nepal Medical Association, 2023)
The adenosquamous carcinoma of the gallbladder is a rare variant accounting for only 1-4% of all primary gallbladder carcinoma. Regardless of the histological types, all gallbladder carcinomas have silent and rapid progression resulting in delayed diagnosis and poor prognosis. Even with medical and/or surgical interventions, the median survival of patients with adenosquamous carcinoma, one of the histological variants, is less than a year. However, we present a case of adenosquamous carcinoma with an unusually better prognosis. A 70-year-old female patient, after being diagnosed with gallbladder carcinoma was suggested for surgical resection but was lost to follow-up since then. Two years later, the patient presented and was managed with extended cholecystectomy. The slow progression and non-recurrence of the tumour during follow-up for two years after the surgery indicates a better prognosis in this case.